Dynamic Analysis of the Scraper Conveyor under Abnormal Operating Conditions Based on the Vibration and Speed Characteristics - Shoubo Jiang; Weijian Ren; Qinghua Mao; Qingliang Zeng; Pengfei Yu; Kuidong Gao; Liang Wang (Shock and Vibration)
The scraper conveyor is the key coal transportation equipment on the coal mining face. The conveyor often encounters the influence of abnormal working conditions, such as stuck chains, broken chains, and impact loads, which have a great effect on the smooth operation of the scraper chain and seriously affect the safety of coal production. If the chain breaks during the test, the broken link may fly out and hurt the tester. The test risk of the scraper conveyor under abnormal working conditions is relatively large; hence, the test research is impossible to carry out. The combination of experiment and simulation is used to carry out the research. The dynamic characteristic test bed of the chain drive system is created to collect the speed of the sprocket and the acceleration of the scraper. The two groups of data are obtained by simulation, and the accuracy of the simulation is verified by comparing the test data with the simulation data. The dynamic characteristics of the chain drive system under abnormal working conditions are analyzed by simulation. Results show that the longitudinal velocity of the link dramatically changes, the contact force increases by 5.4 times, and the link vibrates under impact loads. When the chain is stuck, the speed of the running direction suddenly changes, and the chainring vibrates. The contact force between the chainrings increases by 7.2 times compared with the smooth operation. When the chain is broken, the acceleration in the running direction of the link dramatically changes. This study provides a basis and reference for the further optimization design of the chain drive system and detection of the abnormal working conditions.